Global Economic and Trade Landscape Reshaping and High-Quality Belt and Road Cooperation - Xiujun, Xu (Napredak, 2024)
The global economic and trade landscape is changing, while methods of cooperation are being adjusted to trends. This paper is focused on the Belt and Road Initiative through reflections on the global tendencies and crises during the COVID-19 pandemic. Analyzing five new features of profound economic restructuring of the market, the author points to the rise of the developing countries and the increase in international investments, but also to the increasingly evident rise of digital services. Against the backdrop of deep planetary restructuring, the Belt and Road cooperation has an increasingly important role in the following aspects: first, it provides a strong impetus to global economic and trade growth; second, it taps into the huge potential of the global economic and trade cooperation because the participating countries will use their advantages and encourage mutual potentials through strategic and political connectivity; third, the participating countries build a global economic and trade partnership in the new era; and, fourth, they promote the reshaping of the global economic and trade governance system, which is underway.
Keywords: Belt and Road; market restructuring; politicization of economic and trade relations; scientific and technological parks; new direction of global business operations